Feasibility, benefit and risk of systematic intraoperative cholangiogram in patients undergoing emergency cholecystectomy. - Pouya Iranmanesh; Olivier Tobler; Sandra De Sousa; Axel Andres; Jean-Louis Frossard; Philippe Morel; Christian Toso (PLoS ONE)
Background The role of intraoperative cholangiogram (IOC) during cholecystectomy is debated. The aim of the present study was to evaluate the feasibility, benefit and risk of performing systematic IOC in patients undergoing cholecystectomy for acute gallstone-related disease. Methods Between July 2013 and January 2015, all patients admitted for an acute gallstone-related condition and undergoing same-hospital-stay cholecystectomy were prospectively followed. IOC was systematically attempted and predictors of IOC failure were analyzed. Results Among the 581 enrolled patients, IOC was deliberately not performed in 3 cases. IOC was successful in 509/578 patients (88.1%). The main predictors of IOC failure were age, body mass index, male gender and associated acute cholecystitis. Thirty-two patients with suspected common bile duct stone on IOC underwent 38 unnecessary negative postoperative common bile duct investigations (32/509, 6.3%). There was one IOC-related adverse outcome (mild pancreatitis, 1/578, 0.2%). Conclusions IOC can be successfully and safely performed in the majority of patients undergoing cholecystectomy for acute gallstone-related disease. Although its positive predictive value is suboptimal and results in a number of unnecessary postoperative common bile duct investigations, IOC accurately rules out common bile duct stones in patients with acute gallstone-related conditions.